2003
DOI: 10.1124/jpet.103.059089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoranthene, a Polycyclic Aromatic Hydrocarbon, on cAMP-Dependent Anion Secretion in Human Airway Epithelia

Abstract: The human respiratory tract is constantly exposed to polycyclic aromatic hydrocarbons (PAHs) through inhalation of atmospheric pollutants. We examined the effects of three PAHs (benzo[a]pyrene, anthracene, and fluoranthene) on the airway ion transport, which is essential for lung defense and normal airway function, using human airway epithelia (Calu-3). These three PAHs had no significant effect on the basal short-circuit current (I sc ). However, fluoranthene (1-100 M) applied in the apical compartment potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Similarly, the diol-epoxide metabolites of B(a)P have been found to increase the cytosolic Ca2 + in airway epithelial cells (Jyonouchi et al, 2001). Also, Ito et al (2004) reported that the PAH compound fluoranthene potentates cAMP-dependent anion secretion in airway epithelial cells, thus regulating the membrane potential of these cells.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the diol-epoxide metabolites of B(a)P have been found to increase the cytosolic Ca2 + in airway epithelial cells (Jyonouchi et al, 2001). Also, Ito et al (2004) reported that the PAH compound fluoranthene potentates cAMP-dependent anion secretion in airway epithelial cells, thus regulating the membrane potential of these cells.…”
Section: Discussionmentioning
confidence: 94%
“…This event requires not only the activity of the apical anion channel but also basolateral transporters (Devor et al, 1999;Ito et al, 2004b). The apical CFTR, which is well accepted as a common pathway for HCO 3 Ϫ and Cl Ϫ export (Devor et al, 1999), displays no less than Ϸ60% of maximum conductance at rest, so that the Calu-3 cell is fully capable of anion secretion even under the cAMP-unstimulated state (Moon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Devor et al, 1999;Ito et al, 2004b) reported that the switch between HCO 3 Ϫ secretion and Cl Ϫ secretion is determined by the basolateral membrane potential regulated by a ChTx-sensitive Ca 2ϩ -activated K ϩ channel, KCNN4. Namely, when the basolateral membrane is hyperpolarized by KCNN4 activation, the driving force for HCO 3 Ϫ entry via NBC1 (the Na ϩ -2HCO 3 Ϫ transporter), which carries electrogenically negative charges into the cell, is reduced, whereas the driving force for Cl Ϫ entry across the electroneutral NKCC1 (the Na ϩ -K ϩ -2Cl Ϫ cotransporter) is up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study is to examine and compare the effects of Cordyceps extracts on the ion transport in Calu-3 airway epithelial cell monolayer model system. By using short-circuit current (Isc) measurement, the effects of certain secretagogues on transepithelial ion transport could be demonstrated (Cobb et al, 2003;Ito et al, 2004). Since the chemical markers for Cordyceps sinensis and Cordyceps militaris, adenosine and cordycepin, respectively, have been found to vary in amount between the different parts of fruiting bodies (Shiao et al, 1994;Li et al, 2001b;Chinese Pharmacopoeia Commission, 2005), the efficacies of the extracts from stroma (S) and larva (L)/pupa (P), were also compared in the present study.…”
Section: Introductionmentioning
confidence: 99%